White Snapter Lates Calcarifer Hatchery Techniques at Brackishwater Cultivation Fisheries Center (Bpbap) Situbondo, East Java. - Miranti, Sevia; Sumsanto, Muhammad (Jurnal Media Akuakultur Indonesia, 2025)
Hatchery activities have several stages, starting with broodstock management, preparation of larval containers, broodstock selection, brood spawning, egg handling, larval rearing, feeding management, water quality management and harvesting. The aim is to find out knowledge about white snapper (Lates calcarifer) hatchery techniques at the Brackish Water Aquaculture Center (BPBAP) Situbondo, East Java. The research method used is the descriptive method. The research results showed that the number of broodstock used in the natural spawning process was 84 with a ratio of 1:2, carried out twice during the dark and bright months at night. The harvested eggs were spread in rectangular concrete tanks for 17-18 hours and the HR (Hatching Rate) was calculated with a yield of 96%. Feeding D2-D30 larvae is given 2 times a day with types of feed in the form of natural and artificial feed, D23-D35 larvae feed is given once every 2 hours in the form of artificial feed. The results of measuring water quality parameters were a pH value of 7.75, a salinity value of 30 ppt, a temperature value of 31oC, a dissolved oxygen value of 6.12 mg/L and an ammonia value of 0.085 mg/L. Water management is carried out by siphoning and changing the water according to the age of the larvae. Harvesting of larvae is carried out after grading size and defects and then calculating the SR (Survival Rate) value which is found to be 30%.